EFEKTIVITAS PENGGUNAAN HUKUMAN DALAM MENINGKATKAN MINAT BELAJAR SISWA - Dewi Aulia; Jasiah, Jasiah (Cahaya Ilmu Bangsa Institute, 2024)
The effectiveness of the use of punishment often makes students feel afraid, anxious, and causes hatred towards teachers. However, punishment can also increase students' interest in learning, for example through activities such as working on problems on the board or answering questions that have been taught by the teacher. This study aims to evaluate the effectiveness of the use of punishment in increasing students' interest in learning. The method used is descriptive qualitative, which means that this study relies on data collection techniques through in-depth interviews with key informants and other informants. From this study, it is expected to be explained about (1) how students respond to the use of punishment, and (2) whether the punishment can increase students' interest in learning. The results of the study showed differences in the use of punishment that can increase students' interest in learning.